(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
Omanaster imbricatus is a new genu s and species of Sakmarian (Early Permian) asteroids collected from the basal Pachycyrtella Bed of the Saiwan Formation of Oman, Arabian Peninsula; the family Omanasteridae is recognized. Late Paleozoic and especially Permian asteroids are rare and O. imbricatus differs significantly from those previously described, thereby providing an important addition to known late Paleozoic diversity. Unfortunately the single available specimen is incomplete with remaining ossicles both leached and partially fused, and available data are limited. Adambulacral form and arrangement of O. imbricatus are both suggestive of corresponding expressions of certain earlier Paleozoic species and unlike those of the crown-group, suggesting an enduring Paleozoic lineage but one not phylogenetically a part of the Mesozoic diversification. The Pachycyrtella Bed has been interpreted as recording a succession of pioneer palaeocommunities colonizing a turbulent, shallow-water settingaffected by oscillatory flows. The apparently flattened appearance of O. imbricatus is suggestive of appearances of certain Cretaceous and extant species recovered from similar environments thus suggesting both homoplasy and the versatility of asteroid evolution across extended spans of geologic time.